Giant Paraganglioma Complicated With Catecholamine Crisis and Catecholamine Cardiomyopathy: A Case Report and Review of the Literature - Ma, Xiangping; Chen, Zhen; Xia, Peng; Zhang, Chunmei; Yan, Keqiang; Fan, Yidong; Wang, Yingli; Ti, Yun; Bu, Peili (Frontiers in Endocrinology, 2022)
Background Pheochromocytomas and paragangliomas (PPGL) are rare neuroendocrine tumors which overproduce catecholamines. Heart failure and myocardial infarction caused by paraganglioma complicated with catecholamine crisis are the most common causes of death in PPGL patients before surgery. When giant paraganglioma is complicated with catecholamine crisis, treatment brooks no delay. Case Summary A 49-year-old man had episodic sweating, tachycardia with irregular pulse, and headaches 5 days before, and then showed up with chest pain and wheezing for 1 day. Meanwhile, he developed symptoms of recurrent severe abdominal pain and loss of consciousness, and his blood pressure was severely unstable (from 70/40 to 300/200 mmHg). First, the electrocardiogram showed ventricular tachycardia, and then we noticed the waves of ST-segment elevation, but we did not find significant abnormalities in coronary angiography. Abdominal CT and MRI revealed a giant lesion with bleeding or infection in the retroperitoneal adrenal area. These imaging findings were confirmed during surgery, and there was vascular adhesion between the retroperitoneal tumor and the inferior vena cava and left and right renal vein. After the successful resection of the tumor, postoperative pathology confirmed paraganglioma, and the patient pulled through and was discharged quickly. Discussion This is a rare case of giant paraganglioma complicated with catecholamine crisis and catecholamine cardiomyopathy. We can diagnosis this disease greatly by elevated norepinephrine, and it is a gold biochemical standard at present. Standard treatment is surgical resection, which is effective in treating this rare neuroendocrine tumor.